Reasons of the delayed vaccination, recommendations and safety of vaccination in children with congenital heart disease in Zhejiang, China - Mingyan Li; Chai Ji; Yan Zeng; Dan Yao; Xia Wang; Jie Shao (Taylor & Francis Group, 2021)
There has been a considerable controversy about vaccination practices in Children with congenital heart disease (CHD) in China. This study aims to identify the reasons for deferring vaccination among the patient population attending the Vaccination Consultation Clinic in Zhejiang Province and the safety of their vaccination. We analyzed the data of 2442 children with CHD, who visited to our clinic from January 2016 to March 2019. A questionnaire survey was conducted to investigate the reasons for their delayed vaccination. Information about the following vaccination and Adverse Events Following Immunization (AEFI) was collected. Most of the enrolled children did not receive vaccines on time before consultation. The reasons for their deferring vaccination included: 1. Providers in the community health center refused to administer vaccines (77.6%); 2. Parents' concerns about the safety of vaccines (19.0%); 3. Parents' doubts about the efficiency of vaccines after certain drug applications (3.4%). According to the evaluation reports issued by the Vaccination Consultation Clinic, 83.7% of CHD children were recommended to be vaccinated on the nationally recommended schedule, 14.4% were recommended to defer some specific vaccination, and 1.9% were recommended to defer all vaccination. Among the group who received vaccines on nationally recommended schedule, the AEFI rate was 33.5/100 000. No rare or serious rare vaccine reactions were observed. Our study provides evidence that routine vaccination is safe in the majority of this patient population.